Characterization of multi-scale structure and thermal properties of Indica rice starch with different amylose contents. Issue 109 (10th November 2016) - Li, Zhihang; Kong, Xiangli; Zhou, Xianrong; Zhong, Kui; Zhou, Sumei; Liu, Xingxun
Abstract : Fully understanding the relationship between multi-scale structure and thermal properties of rice starch is important for starch-based food processing. Abstract : Fully understanding the relationship between multi-scale structure and thermal properties of rice starch is important for starch-based food processing. Multi-scale structures of Indica rice starch were studied from molecules to aggregation structure. Gel-permeation chromatography (GPC) and high-performance anion-exchange chromatography (HPAEC) both show that the amylopectin from debranched rice starch exhibits bimodal distributions. Compared with amylose-rich rice starch, amylopectin-rich rice starch had the highest molar- and weight-based ratio of fraction fa′ (DP 6–12) and lower molar-based ratios of fractions fb′3 (DP ≥ 37). X-ray diffraction (XRD) and small angle X-ray scattering (SAXS) confirm that amylopectin-rich starch has the highest crystallinity and scattering intensity. Differential scanning calorimetry (DSC) results show that amylopectin-rich starch has the highest onset and peak gelatinization temperatures; however, there is no significant difference in enthalpy, which may be due to the irregular double helix. Rapid visco-analysis (RVA) shows amylose-rich starch has a higher final and setback viscosity, which may be due to amylose molecule entanglement in starch gel and higher retrogradation ability.